Lgr5+ intestinal stem cell sorting and organoid culture. Issue 2 (12th March 2019) - Liu, Ruixue; Li, Haifeng; Cai, Juan; Wei, Qiang; Han, Xiaonan
Abstract: Intestinal epithelial stem cells (IESCs) are one of the most rapidly self‐renewing and proliferating adult stem cells. The IESCs reside at the bottom of intestinal and colonic crypts, giving rise to all intestinal epithelial lineages and maintaining intestinal epithelial replenishment. The technique of three‐dimensional culture based upon intestinal stem cell biology has been recently developed to study gastrointestinal development and disease pathogenesis. Here, we summarize the techniques used to isolate Lgr5‐positive IESCs to form the enteroids from intestine or colonoids from colon, and present the means to examine these organoid functions. This study will provide a simple and practical way for producing intestinal tissues in the laboratory.